Relevance of Immunohistochemistry for Tumorigenic Tumor-Infiltrating Neutrophils and Reverse Polarity in Colonic Micropapillary Adenocarcinoma: A Case Report - Kazumori Arai; Kensuke Shimazaki; Koji Takahashi; Hiroyuki Hazama; Ko Ohata; Akihiro Sonoda; Tomohiro Iwasaki; Junichi Sakane (Case Reports in Pathology)
Similar to that in other organs, colorectal micropapillary adenocarcinoma (MPA) shows aggressive biological characteristics and reverse polarity (RP). Inhibiting the RP may reduce cancer aggressiveness; however, the pathogenesis of RP remains unclear. We encountered a case of colorectal MPA with tumor-infiltrating neutrophils (TINs), which were suspected to be involved in micropapillary morphogenesis. We examined the case using immunohistochemistry, including luminal differentiation (LD) markers. Numerous TINs were found within the background MPA tumor components, and there were scattered tumor cell detachments from the stroma and disruption of glandular structures. Furthermore, the ruptured lumens were connected to the lacunar stromal spaces created by the tumor cell detachment, and floating isolated tumor cell clusters were observed. Immunohistochemistry suggested that most of the TINs had immunosuppressive and tumor-promoting properties and that the tumor cells that have lost adhesion to the stroma and/or intercellular contacts acquired new LD. Such tumor cell changes have been observed in our previous report on tumors with frequent apoptosis. Based on this case, we suggested that (1) the essence of RP in MPA comprises new LD/apical polarity in tumor cells, which have lost glandular polarity secondary to exfoliative and destructive changes, and (2) the cause of RP might be multifactorial.